Study of HBV and HCV among the Libyan population in Bani Waleed City, Libya - Zahrah M. Eisay; Samira D. Ameigal; Mostafa M. Abdoarrahem; Salheen Grimida; Ahmed. A. Ageel; Hamza Khalifa Ibrahim (African Journal of Advanced Pure and Applied Sciences, 2023)
Hepatitis viral infection is an important burden for healthcare services worldwide. The incidence of HBV and HCV differ between different countries, and even within regions of the same country. The study aimed to investigate the prevalence of viral infection (HBV and HCV) among the Libyan population in Bani Waleed city. The study is cross-sectional and analyzed the incidence of HBV and HCV in Bani Waleed City during the period from 2014 to 2020. 239 cases of viral hepatitis were examined and identified over the study period. The frequency of HBV and HCV was 67.36% and 32.64% respectively, whereas the frequency of co-infection was found to be 3.77%. The results illustrated that the infection rate in males at 53.97% and it was slightly higher than in females 49.79% among age groups between 15 and 75 years. To conclude, the study showed that the prevalence of viral hepatitis in Bani Waleed city is not high, however, further studies are needed to establish the spread ratio in the society.